2013
DOI: 10.17660/actahortic.2013.986.16
|View full text |Cite
|
Sign up to set email alerts
|

Why Sustainable Management of Xanthomonas Wilt of Banana in East and Central Africa Has Been Elusive

Abstract: Banana is an important food and cash crop and constitutes a large proportion of the total crop production in East and Central African (ECA) countries. Banana production has been threatened by Xanthomonas wilt (BXW) disease caused by the bacterium Xanthomonas campestris pv. musacearum. Besides being a threat to food security in the region, the disease has severe economic implications, which emanate from yield losses and management costs. Without proper management, yields in affected areas are reduced to zero. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 10 publications
(19 reference statements)
1
31
0
Order By: Relevance
“…1). The predominance of Xanthomonas wilt incidence and severity in the brewing banana type have also been previously demonstrated (Tripathi et al 2009); this is mainly due to high sugar content in the flower nectar, which attracts a diversity of insects (Tinzaara et al 2011). This study showed a significant association of Xanthomonas wilt severity with the type of banana cultivars (p = 0.005), where the severity was three and seven times lower in farms with a mixture of both indigenous and improved cultivars compared with farms with either improved or indigenous cultivars alone, respectively ( Table 1).…”
Section: Relationship Between Banana Farming Practices and Agro-ecolomentioning
confidence: 71%
See 3 more Smart Citations
“…1). The predominance of Xanthomonas wilt incidence and severity in the brewing banana type have also been previously demonstrated (Tripathi et al 2009); this is mainly due to high sugar content in the flower nectar, which attracts a diversity of insects (Tinzaara et al 2011). This study showed a significant association of Xanthomonas wilt severity with the type of banana cultivars (p = 0.005), where the severity was three and seven times lower in farms with a mixture of both indigenous and improved cultivars compared with farms with either improved or indigenous cultivars alone, respectively ( Table 1).…”
Section: Relationship Between Banana Farming Practices and Agro-ecolomentioning
confidence: 71%
“…A similar pattern was observed in the Kagera region of Tanzania (Shimwela et al 2016). The continued spread of banana Xanthomonas wilt in East and Central Africa can be attributed to inappropriate application of management practices, lack of appropriate methods for farm tools disinfection, and failure in applying regulations and quarantine measures (Tinzaara et al 2011). It was also noted that many farmers abandoned control measures because they were stunned by the devastation of the disease (Tushemereirwe et al 2008).…”
Section: Distribution Of Banana Xanthomonas Wiltmentioning
confidence: 99%
See 2 more Smart Citations
“…This suggests the need for mobilization and sensitization at community level. The approach of engaging the community to own the problem contributed to the success in BXW management in Uganda (Kubiriba et al, 2012;Tinzaara et al 2013;Ochola et al, 2015). This would include engaging locals in the bid for zero tolerance of Xanthomonas wilt by eliminating any sources of inoculum through effective implementation of control measures backed-up by community by-laws that most efficiently brings to book errant farmers who hesitate to manage the disease.…”
Section: Rwandamentioning
confidence: 99%